Renal arterial embolization: Indications, angiographic findings, and outcomes in a series of 170 patients - Hashim Mohamed Farg; Mohamed Elawdy; Karim Ali Soliman; Mohamed Ali Badawy; Ali Elsorougy; Tarek Mohsen; Tarek El-Diasty; Abdalla Abdelhamid (Current Urology, 2023)
Abstract. Background. The lack of overall experience and reporting on angiographic findings in previously published studies of renal arterial embolization (RAE) compelled us to report our overall experience on a series of patients. Materials and methods. A retrospective study was performed analyzing data of patients enrolled for RAE between 2010 and 2019. History, physical examination, and laboratory data were reviewed for all patients. Abdominal ultrasound was the initial imaging study, and all patients underwent subsequent computed tomography or magnetic resonance imaging. The outcome of RAE was determined based on radiographic and clinical findings. Results. Data from 202 patients were analyzed, with a mean age of 45 ± 15 years, and 71.3% of patients were male. Iatrogenic injury was the most common indication for RAE (54%), followed by renal tumors, trauma, and spontaneous, in 27.7%, 10.4%, and 8.4% of patients, respectively. Renal angiography revealing pseudoaneurysm alone or with other pathology in the lower pole of the kidney was the most common finding (40.6%), whereas no lesions were identified on angiography in 32 patients (15.8%), after which RAE was subsequently aborted. Renal arterial embolization was successful in 158 of 170 patients (92.9%) after 1 or more trials (maximum of 4). Microcoil alone or with other embolic materials was the most commonly used material for embolization (85%). Conclusions. Iatrogenic injury was the most common indication for RAE. Pseudoaneurysm alone or with other lesions was the most common lesion on renal angiography; however, angiography showed a negative result in 16% of patients, even those with symptoms. When lesions are present on angiography, the overall success of repeated trials of RAE reached 92.9%.